Morphology comparison of swiftlet species from different habitat in Malaysia - Looi, Qi Hao; Ideris, Aini; Omar, Abdul Rahman (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
In Malaysia, nest of Aerodramus fuciphagus (white-nest swiftlet) and Aerodramus maximus (black-nest swiftlet) are harvested for commercial purposes as one of most valuable animal product. Swiftlet taxonomy has been controversial due to numerous undefined parameters. Morphological differences between swiftlet species from different habitats remain unclear. This study found that A. fuciphagus from natural habitat are generally larger in size compared to man-made habitat and A. maximus are larger compared to A. fuciphagus. We postulated the different in body size is due to dietary behavior of the swiftlets.